Moral Foundations as Predictors of Academic Success: Examining GPA and Subject Preferences in Middle Adolescents - Stastna, Kamila (ETHICS IN PROGRESS, 2025)
This study explores relationships between adolescents’ moral foundations and academic outcomes, extending existing psychological frameworks into educational research. A sample of 192 German high school students (aged 15–17) completed the Moral Foundations Questionnaire, although the analyses specifically focused on the Care, Fairness, and Authority foundations based on theoretical relevance to educational contexts. Academic achievement (grade point average, GPA) and subject preferences were measured through self-reported grades and subject rankings. Data were analyzed using non-parametric correlations, ordinal logistic regression, and group comparisons. Results indicated that higher scores in the Care foundation were significantly associated with better GPA, whereas Fairness showed no significant correlation. Moreover, students expressing dislike for natural sciences displayed significantly higher Authority foundation scores. These results suggest that specific moral foundations may be relevant in shaping academic performance and subject preferences among adolescents. Future studies should further explore underlying mechanisms to inform targeted educational practices.